Direitos lgbt: os princípios de Yogyakarta e a sua receptividade nas fundamentações do Supremo Tribunal Federal - NASCIMENTO, Éden Sousa (2022)
Bearing in mind that Brazil is a country where members of the LGBT community gain most of their rights through the Judiciary and its jurisprudential constructions, research on the principles of Yogyakarta and its receptivity in the foundations of the Supreme Federal Court, the in order to identify how these principles influence the decisions of the Brazilian Court. For that, it is necessary to evaluate the evolution of the LGBT movement and its conquests of rights in Brazil, to elucidate the importance of the Yogyakarta Principles for the LGBT movement, as well as the process that preceded it in international protection systems and to identify how this letter of principles has been used by the Federal Supreme Court. An inductive method research is then carried out, so that, through jurisprudential research, it is possible to infer this universal truth. Given this, it appears that the LGBT movement has struggled for decades for recognition as citizens of law; the Yogyakarta Principles are an important part in the process that triggered deliberations on sexual orientation and gender identity at the international level; the STF uses this letter of principles as a basis in its decisions, giving it an important legal value, which imposes the realization that the Yogyakarta Principles can be recognized as general international law custom on the national scene.